STRATEGI PENGEMBANGAN HUTAN PINUS GRENDEN BERBASIS EKOWISATA DI MAGELANG - Susanto, Dwiyono Rudi; Kiswantoro, Amin (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
This research aims to determine the right strategy in developing ecotourism-based Pine Grenden Forest in Magelang City. This research uses descriptive method with a qualitative approach. Data collection is done by using observations, interviews, and questionnaires. This research using non probability sampling technique with a sample of 100 people in the Grenden Pine Forest. The sampling method in this study uses incidental sampling. Data collected were analyzed using SWOT analysis. The results of this study obtained several strategies that can be applied by the managers of the Grenden Pine Forest, such as (1) making instagramable photo spots and showing the characteristics of the Pine Grenden Forest, (2) in collaboration with the Mount Merbabu National Park to make educational tours related with the introduction of Pine Trees and Merbabu animals, (3) manufacturing of Grenden's distinctive tourism products, such as food and souvenirs, (4) planting trees and capturing endemic Merbabu animals.